(untitled) (Damascus University Journal of agriculture sciences, 2023)
This research was conducted at the Department of Food Sciences, Faculty of Agriculture, Damascus University, and the Central Grain Laboratory, Ministry of Internal Trade and Consumer Protection, with the aim of determining the changes in the physicochemical and thermal properties (amylograph properties) of two types of locally produced flour (high-quality flour and standard flour) when adding two types of surfactants (monoglyceride and sodium sterol lactate) by the ratios (0, 0.2, 0.4 and 0.6%). The analysis results of the flour physicochemical properties showed that there were no significant differences between the two types of surfactants for each flour type, as the addition of surfactants did not lead to any change in both moisture content and total protein content. On the contrary, the addition of surfactants resulted in a significant increase in the quantitative and qualitative indices of gluten, ash content and flour colour degree. On the other hand, the effect degree of the two studied types of surfactants differed on the thermal properties of flour. The gelatinization onset time decreased when monoglyceride was added, while it increased when sodium sterol lactate was added. In addition, changing the flour type did not change the mechanism of qualitative effect of the surfactants used in this research on the thermal properties of the wheat flour suspension, and thus the similarities between the two types of flour confirm the fact that the starch fraction, which constitutes 65% of the wheat grain weight, exerted a main effect on the hot flour suspension viscosity. The differences between the two types of the studied surfactants in the pasting properties were due to the interactions between these substances and the starch molecule, which was mainly attributed to the length of the carbon chain of the surfactants that determined the type of effect observed in the studied properties.